Little League shoulder in a 15-year-old male baseball pitcher - Zipser, M. C.; Sum, J. C.; Wilcox, A. G. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
A 15-year-old baseball pitcher presented to physical therapy with a 1-week history of acute right shoulder pain experienced during the acceleration phase of throwing. The week after physical therapy evaluation, the patient returned with radiographs and magnetic resonance imaging results that revealed lateral physeal widening with adjacent edema. Additionally, a nondisplaced labral tear was noted. In this case, imaging was necessary for an accurate diagnosis of lateral physeal widening, commonly referred to as "Little League shoulder."